Scorpion (Buthus martensii Karsch) in Chinese medicine: a review of traditional uses, chemical constituents, pharmacology, and toxicology - Liu, Meng-Han; Zhu, Juan-Juan; Lu, Qi; Qu, Zhen-Ni; Zhou, Qiao; Zhang, Lei; Dai, Yan-Peng; Shi, Dian-Hua (Frontiers in Pharmacology, 2025)
The processed Buthus martensii Karsch scorpions, commonly called Quanxie or Scorpio, have been a valuable traditional medicine for over a millennium, with documented use dating back to 935-960 AD. Traditionally employed in treating rheumatism, epilepsy, stroke, and chronic pain, Scorpio contains diverse chemical constituents, including venom, steroid derivatives, alkaloids, amino acids, and nucleosides. Modern pharmacological studies have identified active components, particularly venom and proteins, that exhibit analgesic, antitumor, antiepileptic, and antithrombotic properties. However, these same active ingredients can also induce neurotoxicity and autonomic dysfunction, with overdose leading to such adverse effects. Consequently, numerous processing methods have emerged to mitigate toxicity while preserving pharmacological activity. Despite these advances, key research gaps persist: modern studies overly rely on isolated venom components (with insufficient attention to multi-constituent interactions in processed whole scorpions), high-quality clinical trials are lacking in the functional research on active ingredients, and the mechanisms underlying processing-induced detoxification remain unclear.